BAY LEAF (SYZYGIUM POLYANTHUM) EXTRACT GEL EFFECT ON TNF- Î‘ EXPRESSION IN TRAUMATIC ULCERS HEALING PROCESS - Savira, Annisha; Mujayanto, Rochman; Amurwaningsih, Musri (Faculty of Dentistry, Universitas Islam Sultan Agung, 2020)
Background: Traumatic ulcers were injuries that occur to the epithelium and basement membrane, due to physical, mechanical, or chemical trauma. The healing process of traumatic ulcers was divided into three main phases, namely inflammatory, proliferation, and maturation phase. TNF-Î± as a proinflammatory mediator worked 2-3 days which later would be replaced by an anti-inflammatory mediator. This research aimed to determine the impact of bay leaf extract gel, which had a very high anti-inflammatory content, on TNF-Î± expression in accelerating the ulcers healing process.Method: This research method was an in vivo experimental laboratory research using a post-test only control design. The sample consists of 20 rats divided into four groups, namely, the control group on day 1, control groups on day 3, treatment groups on 1st day, and treatment groups on 3rd day. Rats were made traumatic ulcers on the lower lip mucosa and were given bay leaf extract gel in the morning and evening. The tissue was then made into a histological preparation and given immunohistochemical staining to see TNF-Î±.Result: The results showed the mean of cells expressing TNF-Î± in the bay leaf gel extract group on the 1st and 3rd days has P> 0.05. Independent T-test on 1st day dan 3rd group showed a significant difference in TNF-Î± expression in the control and treatment groups.Conclusion: The conclusion obtained in this study was bay leaf extract gel had a significant effect on the expression of TNF-Î± in the traumatic ulcers healing process.